2016
DOI: 10.1101/gr.210609.116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic compendium of 1511 human brains available through the UK Medical Research Council Brain Banks Network Resource

Abstract: Given the central role of genetic factors in the pathogenesis of common neurodegenerative disorders, it is critical that mechanistic studies in human tissue are interpreted in a genetically enlightened context. To address this, we performed exome sequencing and copy number variant analysis on 1511 frozen human brains with a diagnosis of Alzheimer's disease (AD, n = 289), frontotemporal dementia/amyotrophic lateral sclerosis (FTD/ALS, n = 252), Creutzfeldt-Jakob disease (CJD, n = 239), Parkinson's disease (PD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…For the UK Brain Bank Network (UKBBN), we ran a survival analysis against the age at death (Keogh et al, 2017). For UKB subjects, we tested the effects of mutations on lifespan and healthspan.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…For the UK Brain Bank Network (UKBBN), we ran a survival analysis against the age at death (Keogh et al, 2017). For UKB subjects, we tested the effects of mutations on lifespan and healthspan.…”
Section: Study Design and Data Sourcesmentioning
confidence: 99%
“…The APOE variants, especially its ε4 allele, are the most studied among all genetic variants in people with LBD . Apolipoprotein E (APOE) is involved in cholesterol mobilisation and redistribution during neuronal growth and injury, and it may promote β‐amyloid aggregation .…”
Section: Resultsmentioning
confidence: 99%
“…GBA variants are likely to increase the risk of earlier onset cognitive impairment in PD. Six studies including four good quality studies have reported statistically significant associations between DLB and GBA variants including rs2230288, rs76763715, rs368060, rs35749011, and rs421016 (Table ). Moreover, two studies have reported statistically significant associations between GBA variants and PDD (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We characterized the effect of ultra-rare damaging mutation burden on human traits associated with longevity. For the UK Brain Bank Network (UKBBN) postmortem samples, we run a survival analysis against the age at death 15 . For UKB subjects, we tested the effect of mutations on the remaining lifespan (or simply lifespan), that is survival within the available follow-up of eleven years.…”
Section: Resultsmentioning
confidence: 99%